Anti-static agent

The lignin derivative compound in the antistatic agent addresses the variability of antistatic performance across resin compositions by enhancing surface resistivity and cellulose dispersibility, ensuring effective antistatic properties in resin compositions.

JP2025004615APending Publication Date: 2025-01-15NIPPON PAPER IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023104416
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

Conventional kneading type antistatic agents do not exhibit sufficient antistatic effect across various resin compositions.

Method used

An antistatic agent containing a lignin derivative compound with specific structural units derived from ligninsulfonic acid and aromatic water-soluble compounds with alkylene oxide chains, optimized in weight ratios and molecular weights, is used to enhance antistatic performance.

Benefits of technology

The lignin derivative compound provides consistent antistatic effects regardless of resin composition, improving both surface resistivity and cellulose dispersibility in resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004615000004
    Figure 2025004615000004
  • Figure 2025004615000001
    Figure 2025004615000001
  • Figure 2025004615000002
    Figure 2025004615000002
Patent Text Reader

Abstract

To provide a kneadable anti-static agent which can exhibit an excellent anti-static effect regardless of the resin composition.SOLUTION: The present invention provides an anti-static agent for resin that contains a lignin derivative compound containing a constituent unit (I) derived from a ligninsulfonic acid compound and a constituent unit (II) derived from an aromatic water-soluble compound that includes at least an aromatic water-soluble compound having an alkylene oxide chain, as well as applications thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antistatic agent. [Background technology]

[0002] As a method for preventing static electricity in resin molded products, antistatic agents have been developed that are kneaded into resin materials. For example, Patent Document 1 describes that a polymeric antistatic agent for thermoplastic resins containing a polyurethane compound does not lose its antistatic ability even after washing with water. Patent Document 2 describes that a combination of a specific anionic surfactant and a nonionic surfactant exhibits an excellent antistatic effect. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-178042 A [Patent Document 2] JP 2018-123306 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional knead-type antistatic agents sometimes do not have sufficient antistatic effect depending on the resin composition. Therefore, an object of the present invention is to provide a knead-type antistatic agent that can exhibit good antistatic effect regardless of the resin composition. [Means for solving the problem]

[0005] The present invention provides the following [1] to

[10] . [1] An antistatic agent for resins, comprising a lignin derivative compound having the following structural units (I) and (II): (I): Structural unit derived from lignosulfonic acid compounds (II): A structural unit derived from an aromatic water-soluble compound that contains at least an aromatic water-soluble compound having an alkylene oxide chain. [2] The antistatic agent according to [1], wherein the aromatic water-soluble compound having an alkylene oxide chain includes an aromatic water-soluble compound having an alkylene oxide chain with an average added mole number of 25 or more of alkylene oxide. [3] The antistatic agent according to [1] or [2], wherein the weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is 1 / 99 to 99 / 1. [4] The antistatic agent according to any one of [1] to [3], wherein the aromatic water-soluble compound further comprises an aromatic compound having a carboxyl group and / or an aromatic compound having a sulfo group. [5] The antistatic agent according to any one of [1] to [4], wherein the lignin derivative compound represented by the following formula has a peak area ratio of a polymer component of 80% or more. Peak area ratio of high molecular weight components = (area value of high molecular weight components in GPC chart (280 nm)) / (area value of all components in GPC chart (280 nm)) [6] A method for treating a resin surface, comprising kneading the antistatic agent according to [1] or [2] into a resin substrate. [7] A resin composition comprising the antistatic agent according to any one of [1] to [5] and a resin substrate. [8] The resin composition according to [7], wherein the content of the antistatic agent relative to 100% by weight of the resin substrate is 1.5% by weight or more. [9] The resin composition according to [7] or [8], wherein the resin substrate further contains a cellulose-based material.

[10] A molded article of the resin composition according to [7] or [8]. Effect of the Invention

[0006] According to the present invention, it is possible to provide an antistatic agent that can exhibit a good antistatic effect regardless of the resin composition. [Brief description of the drawings]

[0007] [Figure 1]FIG. 1 is an image of a GPC chart (UV detection wavelength: 280 nm) of a lignin derivative compound for explaining the peak area ratio of high molecular weight components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [1. Antistatic agents for resins] The antistatic agent for resin contains the following lignin derivative compound as an active ingredient.

[0009] [1.1 Building blocks of lignin derivative compounds] The lignin derivative compound is a polymer containing at least the structural units (I) and (II). Since lignin, which is the main skeleton of the structural unit (I), has a very complicated molecular structure, it is difficult to uniformly specify the chemical structure of the lignin derivative compound by a general formula or the like.

[0010] -Structural unit (I)- The structural unit (I) is a structural unit derived from a lignosulfonic acid compound. Lignosulfonic acid compounds are compounds that have a skeleton in which the carbon at the α-position of the side chain of the hydroxyphenylpropane structure of lignin is cleaved to introduce a sulfo group (sulfonic acid group). The structure of the skeleton is shown in formula (1). [ka]

[0011] The lignosulfonic acid compound may be a modified product of a compound having the skeleton represented by the above formula (1) (hereinafter, also referred to as a "modified lignosulfonic acid compound"). The modification method is not particularly limited, and examples thereof include chemical modification methods such as hydrolysis, alkylation, alkoxylation, sulfonation, sulfonate esterification, sulfomethylation, aminomethylation, and desulfonation; and a method of molecular weight fractionation of a lignosulfonic acid compound by ultrafiltration. Among these, the chemical modification method is preferably one or more modification methods selected from hydrolysis, alkoxylation, desulfonation, and alkylation.

[0012] The lignosulfonic acid compound may be in the form of a salt. Examples of the salt include monovalent metal salts, divalent metal salts, ammonium salts, and organic ammonium salts. Among these, calcium salts, magnesium salts, sodium salts, and mixed calcium-sodium salts are preferred.

[0013] A lignin sulfonate compound usually has at least one functional group site capable of reacting with the aromatic water-soluble compound constituting the structural unit (II). Examples of such sites include a carboxyl group, a hydroxyl group (phenolic hydroxyl group, alcoholic hydroxyl group), a thiol group, a sulfo group, an aromatic ring, an ether bond, and an alkyl chain. In one embodiment, the functional group site of the lignin sulfonate compound is bonded directly or via a condensing agent such as formaldehyde with the aromatic water-soluble compound to form a lignin derivative compound.

[0014] The method of producing the lignosulfonic acid compound and its origin are not particularly limited, and it may be either a natural product or a synthetic product. Lignosulfonic acid compounds are one of the main components of the waste liquor of sulfite pulp obtained by cooking wood under acidic conditions. Therefore, lignosulfonic acid compounds derived from sulfite pulp waste liquor may be used.

[0015] -Structural unit (II)- The structural unit (II) is a structural unit derived from a water-soluble aromatic compound. The aromatic water-soluble compound means a compound that contains at least one aromatic skeleton and is water-soluble. The aromatic water-soluble compound is preferably a compound that can bond with a functional group contained in a lignosulfonic acid compound by chemical reaction, and more preferably a compound that can react with a functional group contained in a lignosulfonic acid compound as a main component of sulfite pulp waste liquor. The type of chemical reaction is not particularly limited, and examples thereof include radical reaction, ionic bond, coordinate bond, condensation reaction, reaction involving hydrolysis, reaction involving dehydration, reaction involving oxidation, reaction involving reduction, and reaction involving neutralization.

[0016] The aromatic water-soluble compound preferably has an alkylene oxide chain or a polar group. This can improve the reactivity when forming a bond between the structural units (I) and (II). The polar group may be an ionic functional group, such as a carboxyl group, a hydroxyl group, a sulfo group, a nitroxyl group, a carbonyl group, a phosphate group, an amino group, or an epoxy group. Anionic functional groups such as a hydroxyl group, a carboxyl group, a sulfo group, or a phosphate group are preferred, and a carboxyl group or a sulfo group is more preferred. The anionic functional group in the lignin derivative compound can be quantitatively and qualitatively observed by instrumental analysis such as NMR or IR.

[0017] Examples of the aromatic water-soluble compound include the following compounds.

[0018] (Water-soluble aromatic compounds having alkylene oxide chains) The number of carbon atoms of the alkylene oxide unit constituting the alkylene oxide chain (group) is not particularly limited, and is usually 2 to 18, preferably 2 to 4, and more preferably 2 to 3. Examples of the alkylene oxide unit include an ethylene oxide unit, a propylene oxide unit, and a butylene oxide unit, and an ethylene oxide unit or a propylene oxide unit is preferred. The average number of moles of the alkylene oxide unit added is usually 20 or more or 25 or more, preferably 30 or more, and more preferably 35 or more. This can improve the dispersibility. The upper limit is preferably 300 or less, more preferably 200 or less, and even more preferably 150 or less. This can suppress the decrease in the dispersion retention. Therefore, the average number of moles added is preferably 20 to 300, or 25 to 300, more preferably 30 to 200, and even more preferably 35 to 150. The above-mentioned average number of moles added is a guideline, and regardless of whether the above-mentioned range is satisfied, the alkylene oxide chain may contain one in which alkylene oxide units are not repeatedly added (monoalkylene oxide group).

[0019] The polyalkylene oxide chain may be composed of one type of alkylene oxide group or two or more types of alkylene oxide groups. The addition form of each alkylene oxide group in the polyalkylene oxide chain composed of two or more types of alkylene oxide groups may be any of random, block, and mixture thereof. The terminal unit of the polyalkylene oxide chain is usually a hydroxyl group, but is not limited thereto, and may be an alkyl ether or a carboxylate ester as long as it does not interfere with the bond with the lignin sulfonic acid compound.

[0020] Examples of aromatic water-soluble compounds having an alkylene oxide chain include oxyalkylene group adducts to aromatic compounds such as phenol, cresol, nonylphenol, naphthol, methylnaphthol, butylnaphthol, bisphenol A, and bisphenol S. More specifically, examples include polyalkylene oxide alkylphenyl ethers, polyalkylene oxide phenyl ethers, polyalkylene oxide alkylnaphthyl ethers, and polyalkylene oxide naphthyl ethers. Among these, benzene ring derivatives are preferred because they can have good co-condensation properties, and at least one of polyalkylene oxide alkylphenyl ethers and polyalkylene oxide phenyl ethers is more preferred, and polyalkylene oxide phenyl ethers (particularly, oxyalkylene group adducts to phenol) (for example, poly(ethylene oxide) monophenyl ether, poly(propylene oxide) monophenyl ether, and the preferred range of the average added mole number of ethylene oxide unit and propylene oxide unit is as described above) are even more preferred. The aromatic water-soluble compound having an alkylene oxide chain may be used alone or in combination of two or more kinds.

[0021] (Aromatic water-soluble compounds having a carboxyl group) Examples of aromatic water-soluble compounds having a carboxyl group include naphthalene ring or benzene ring derivatives having at least one carboxyl group. More specifically, examples include isophthalic acid, oxynaphthoic acid, benzoic acid, hydroxybenzoic acid, and isomers thereof. Because of good reactivity, o-hydroxybenzoic acid, m-hydroxybenzoic acid, and p-hydroxybenzoic acid are preferred, and p-hydroxybenzoic acid is more preferred. The aromatic water-soluble compounds having a carboxyl group may be one type or a combination of two or more types.

[0022] (Water-soluble aromatic compounds having sulfo groups) Examples of aromatic water-soluble compounds having a sulfo group include alkylnaphthalenesulfonic acid, alkylphenolsulfonic acid, aniline sulfonic acid, and alkylbenzenesulfonic acid. More specifically, examples of aromatic water-soluble compounds include naphthalenesulfonic acid, methylnaphthalenesulfonic acid, butylnaphthalenesulfonic acid, phenolsulfonic acid, cresolsulfonic acid, aniline sulfonic acid, benzenesulfonic acid, toluenesulfonic acid, and their isomers and condensates. Examples of condensates include naphthalenesulfonic acid-formaldehyde condensates. Because of their good reactivity, phenol derivatives and aniline sulfonic acid having a sulfo group are preferred, phenolsulfonic acid and aniline sulfonic acid are more preferred, and aniline sulfonic acid is even more preferred. The aromatic water-soluble compounds having a sulfo group may be one type or a combination of two or more types.

[0023] (Other aromatic water-soluble compounds) The other aromatic water-soluble compounds include aromatic water-soluble compounds having no alkylene oxide chain, carboxyl group, or sulfo group, such as (alkyl)phenols such as phenol and cresol. The other aromatic water-soluble compounds may be one type or a combination of two or more types.

[0024] The aromatic water-soluble compound contains at least an aromatic water-soluble compound having an alkylene oxide chain, and it is more preferable to use only an aromatic water-soluble compound having an alkylene oxide chain, or a combination of said compound with an aromatic water-soluble compound having a carboxyl group and / or an aromatic water-soluble compound having a sulfo group.

[0025] The structural unit (I) may be a structural unit derived from one type of aromatic water-soluble compound, or may be a structural unit derived from two or more types. The aromatic water-soluble compound may be a single type or a combination of two or more types, and is preferably an aromatic water-soluble compound having an alkylene oxide chain alone, or a combination of the compound with an aromatic water-soluble compound having a carboxyl group and / or an aromatic water-soluble compound having a sulfo group.

[0026] -Other structural units (III)- The lignin derivative compound may have a structural unit (III) other than the structural units (I) and (II). For example, aromatic compounds other than aromatic water-soluble compounds (e.g., simple aromatic hydrocarbon compounds such as benzene and naphthalene), (poly)alkylene glycol alkenyl ether compounds; water-soluble polyalkylene glycols having hydrogen atoms at both ends, polyoxyalkylene compounds, polycarboxylic acid compounds, and polyester compounds, each of which may be derived from a structural unit (e.g., the polymer block described in WO 2018 / 56124). The structural unit (III) may be one type or a combination of two or more types.

[0027] [1.2 Composition ratio of each structural unit of lignin derivative compound] The weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is usually 1 / 99 to 99 / 1, preferably 2 / 98 to 90 / 10, more preferably 5 / 95 to 70 / 30 or 10 / 90 to 70 / 30, and even more preferably 15 / 85 to 70 / 30. 70~15 / 30~20 (the total of (I) and (II) being 100% by weight).

[0028] When the structural unit (III) is contained, the weight proportion thereof is usually 5% by weight or less, preferably 3% by weight or less, and more preferably 2% by weight or less, relative to 100% by weight of the total of (I) and (II).

[0029] (I) / (II) is defined as (weight of solids of lignosulfonic acid compound before reaction) / (weight of solids of aromatic water-soluble compound before reaction) in the reaction between a lignosulfonic acid compound and a water-soluble aromatic compound, and is measured by this method in the examples described later.

[0030] When the structural unit (II) contains a structural unit derived from a compound other than an aromatic water-soluble compound having an alkylene oxide chain, the ratio of the structural unit derived from an aromatic water-soluble compound having an alkylene oxide chain in the structural unit (II) is usually 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. There is no particular upper limit, and it is sufficient if it is 100% by weight or less.

[0031] The weight ratio of each of the above constituent units corresponds to the ratio of each compound as a raw material used at the start of the reaction.

[0032] [1.3 Salts of lignin derivative compounds] The lignin derivative compound may be any reaction product obtained by the above-mentioned reaction, and may be either a free acid or a neutralized salt thereof. Neutralized salts are preferred because the polymer is easy to store and use. Examples of neutralized salts of the reaction product include alkali metal salts such as sodium salts or potassium salts; alkaline earth metal salts such as calcium salts; ammonium salts; and salts of organic amines.

[0033] [1.4 Physical properties of lignin derivative compounds] -Weight average molecular weight- The weight-average molecular weight of the lignin derivative compound is not particularly limited, but is preferably 1,000 to 500,000, more preferably 2,000 to 300,000, and further preferably 5,000 to 100,000. The weight-average molecular weight in the present invention can be measured by a known method using gel permeation chromatography (GPC) in terms of polyethylene glycol.

[0034] The GPC measurement conditions are exemplified as follows. The values ​​measured in the examples below are also measured under these conditions. Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh or GL Science) Detector: Differential refractometer (Tosoh)

[0035] -Peak area ratio of polymer components- The peak area ratio of the high molecular weight component of the lignin derivative compound is usually 80% or more, preferably 85% or more. The upper limit is 97% or less, more preferably 95% or less. Within this range, the structural units (I) and (II) in the lignin derivative compound are present in a well-balanced manner, and the antistatic effect can be exhibited. In this specification, the peak area ratio of the high molecular weight component means the ratio of the peak area value of the component having a weight average molecular weight of 1,200 or more to the peak area of ​​all components in a chart obtained by using UV (detection wavelength 280 nm) in gel permeation chromatography (GPC) measurement of the lignin derivative compound, and can be calculated by the following formula. Peak area ratio of high molecular weight components = (area value of high molecular weight components in GPC chart (280 nm)) / (area value of all components in GPC chart (280 nm))

[0036] The method of specifying each area value will be described with reference to the GPC chart in FIG. 1. In FIG. 1, point (1) is the elution start point, point (2) is the elution end point, and point (3) is the value corresponding to a weight average molecular weight of 1,200. The area value of the high molecular weight component in the above formula is the intersection of the line (baseline: dotted line in FIG. 1) connecting point (1) and point (2). The area value of all components means the area of ​​the part surrounded by the line (baseline: dotted line in FIG. 1) connecting point (1) and point (2) and the curve from point (1) to point (2). The peak area value of a component having a weight average molecular weight of 1,200 or more means the area of ​​the part surrounded by the part of the baseline from point (1) to point (3), the straight line (dash line in FIG. 1) extending perpendicularly from point (3) to the baseline, and the curve. The measurement conditions of GPC can be the same as those of GPC when measuring the weight average molecular weight described above.

[0037] [1.5 Method for producing lignin derivative compound] The preparation of the lignin derivative may be carried out by any method that involves reacting raw material compounds including a lignin sulfonic acid compound (hereinafter sometimes referred to as compound (i)) and an aromatic water-soluble compound (hereinafter sometimes referred to as compound (ii)). For example, a method of reacting a lignin sulfonic acid compound with an aromatic water-soluble compound may be mentioned. In detail, for example, a method of condensing (e.g., formaldehyde condensation) an aromatic water-soluble compound with a lignin sulfonic acid compound, a radical reaction, or an ionic bond may be mentioned. For example, a method of formaldehyde condensation may be mentioned in which formaldehyde is added to a lignin sulfonic acid compound and bonded to an aromatic water-soluble compound. For example, a method of radical reaction may be mentioned in which a radical initiator is applied to a lignin sulfonic acid compound to abstract a hydrogen radical, and the generated radical is radical-reacted with at least one kind of aromatic water-soluble compound.

[0038] The method for producing the lignosulfonic acid compound as the raw material is not particularly limited, and it can be produced, for example, by a method of extracting it from the waste liquid of sulfite pulp obtained by cooking wood under acidic conditions (for example, a method of filtering the waste liquid, subjecting the obtained filtrate to at least one of an alkali reaction treatment, an air oxidation treatment, and an oxygen treatment as necessary, and then causing precipitation by adjusting the pH, and recovering the precipitate). Furthermore, a powdered product that has been subjected to a drying treatment such as a powder drying treatment may also be used. Being in powder form makes it easy to handle.

[0039] The lignin sulfonic acid compound may be a commercially available product, for example, Vanilex HW (manufactured by Nippon Paper Industries Co., Ltd.), Sunex M (manufactured by Nippon Paper Industries Co., Ltd.), Pearlex NP (manufactured by Nippon Paper Industries Co., Ltd.), or Sunflow RH (manufactured by Nippon Paper Industries Co., Ltd.) The lignin sulfonic acid compound may be in the form of a salt such as a monovalent metal salt, a divalent metal salt, an ammonium salt, or an organic ammonium salt (preferably a monovalent metal salt or a divalent metal salt, more preferably a calcium salt, a magnesium salt, a sodium salt, or a mixed calcium-sodium salt).

[0040] The reaction temperature between the lignosulfonic acid compound and the aromatic compound may be appropriately set depending on the solvent used, and is not particularly limited, but is usually 0 to 200° C., and preferably 45 to 150° C. When a low-boiling compound is used as the reaction solvent, it is preferable to carry out the reaction under pressure using an autoclave in order to improve the reaction rate.

[0041] The reaction form of the lignosulfonic acid compound and the aromatic water-soluble compound may be either a solution reaction or a bulk reaction. In the case of a solution reaction, a solvent may be used. Examples of the solvent include water; alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as cyclohexane and n-hexane; esters such as ethyl acetate; ketones such as acetone and methyl ethyl ketone; and cyclic ethers such as tetrahydrofuran and dioxane. Among them, at least one of water and lower alcohols is preferred, and water is more preferred. This can improve the solubility of the raw material monomer and the resulting copolymer, and can omit the desolvation process. The solvent may be used alone or in combination of two or more (for example, a water-alcohol mixed solvent).

[0042] A defoaming agent may be used during the preparation of the lignin derivative. This makes it possible to suppress foaming during the reaction and to build a uniform reaction system. Examples of the defoaming agent include those containing a nonionic surfactant as an active ingredient.

[0043] In the preparation of the lignin derivative compound, it is preferable to allow the reaction to proceed stably. For this purpose, when the reaction is carried out by solution polymerization, the dissolved oxygen concentration of the solvent used at 25°C may be adjusted to preferably 5 ppm or less, more preferably 0.01 to 4 ppm, even more preferably 0.01 to 2 ppm, and even more preferably 0.01 to 1 ppm. The adjustment of the dissolved oxygen concentration may be carried out in a reaction tank or may be completed before the reaction.

[0044] The progress of the reaction is characterized by a distinct increase in viscosity. When the desired viscosity is reached, the reaction may be stopped by cooling or neutralization.

[0045] In the preparation of the lignin derivative compound, the addition of water may be adjusted to control the condensation viscosity and the condensation time. The pH during the reaction may be adjusted to an appropriate value. The reaction is usually carried out under acidic conditions. When the reaction system is already acidic due to the aromatic compound having a sulfo group and the unreacted acid contained therein, the reaction may be carried out in the acidic region as it is. When the reaction system is not acidic, the reaction may be carried out by adding an acid catalyst such as hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, or p-toluenesulfonic acid in advance. The preferred acid is sulfuric acid, but may be other than the above specific examples and is not limited thereto.

[0046] The reaction rate of the aromatic water-soluble compound is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more. When the reaction rate is 50% or more, the dispersibility of the obtained lignin derivative can be satisfactorily exhibited.

[0047] The reaction rate of the aromatic water-soluble compound can be measured as follows, and is measured in the examples described below. First, in the GPC measurement, when UV (detection wavelength 280 nm) is used, the peak areas before and after the reaction are compared. Next, when the peak area before the reaction (i.e., the peak area of ​​the aromatic water-soluble compound) is [b] and the peak area after the reaction is [a], the reaction rate can be calculated by the formula: ([b]-[a]) / [b]. The GPC measurement conditions can be the same as those for the GPC used in the above-mentioned weight average molecular weight measurement.

[0048] After the condensation reaction is completed, the reaction solution is preferably subjected to post-treatment such as heat treatment at 60 to 120° C. under a pH condition of 8.0 to 13.0, neutralization treatment, and treatment for precipitating the reaction product as a solid by adjusting the pH of the reaction solution (for example, lowering to 1.0 to 4.0, preferably 1.5 to 2.0). The post-treatment is usually performed continuously for about 10 minutes to 3 hours. This can significantly reduce the aldehyde content (for example, formaldehyde content) of the reaction solution. In addition to or instead of the removal of free formaldehyde by the so-called Cannizzaro reaction described above, other methods for reducing excess formaldehyde, for example, known in the field of melamine-formaldehyde resin and phenol-formaldehyde resin chemistry, may be used. Examples of such methods include the addition of a formaldehyde absorbent (addition of a small amount of sodium hydrogen sulfite, addition of hydrogen peroxide).

[0049] In the case of a treatment in which the pH of the reaction solution is adjusted to precipitate the reaction product as a solid, the supernatant salt solution is then separated and removed, and the remaining mostly salt-free free reaction product is redissolved in an amount of water sufficient to obtain the desired solid concentration, thereby obtaining the lignin derivative.

[0050] The neutralization treatment can be carried out using a neutralizing agent capable of neutralizing the reaction product and the catalyst. Examples of the neutralizing agent include basic compounds such as sodium hydroxide, calcium hydroxide, Ba(OH)2, and the like (including salts and hydroxides thereof). As a result, calcium sulfate and barium sulfate, which are less soluble, are formed together with free sulfuric acid, and precipitate in the form of gypsum, etc. Therefore, the precipitate can be separated and removed by subsequent filtration, and a salt-free polymer can be obtained. Furthermore, undesirable sodium sulfate may be separated and removed by dialysis or ultrafiltration.

[0051] In the case where by-products such as sodium sulfate, calcium sulfate, and hydrates thereof are generated in the addition and neutralization of the basic compound, it is preferable to add the basic compound in a heated state after the reaction and maintain the heated state to improve the removal of the by-products. The heating is preferably performed to 40° C. or higher. The time for maintaining the heated state is preferably 30 minutes or more. The concentration of the obtained lignin derivative compound may be adjusted as necessary after the reaction is completed.

[0052] [1.6 Optional components of antistatic agents] The antistatic agent may contain an optional component. The optional components include antistatic components other than the lignin derivative compound, solvents, emulsifiers (surfactants, wetting agents: nonionic, anionic, amphoteric, cationic), antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, flame retardants, plasticizers, pigments, dyes, dye dispersants, chelating agents, unreacted compounds (i) and (ii), and the like. By including the unreacted compound (ii) as an optional component, the antistatic effect can be further improved. The amount of the unreacted compound (ii) is preferably less than the converted weight of the structural unit (II) in the lignin derivative compound, more preferably 3 / 7 or less.

[0053] [2. How to use antistatic agents] The antistatic agent can be used to prevent static electricity in resins. As a method for obtaining an antistatic effect in resins, for example, a method of kneading the antistatic agent into a resin base material containing a resin material can be mentioned.

[0054] [2.1 Resin materials] The resin material may be either a thermoplastic resin or a thermosetting resin, but is preferably a thermoplastic resin. For example, polyolefin resins such as polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, and ethylene-ethyl acrylate copolymer, halogen-containing resins such as polyvinyl chloride, polyvinylidene chloride, polyvinylidene fluoride, and polytetrafluoroethylene, styrene-based resins such as polyacrylonitrile, polystyrene, and copolymers of styrene and other monomers (for example, acrylonitrile-styrene (AS) resin, acrylonitrile-butadiene-styrene (ABS) resin), polyester-based resins such as polyester, polyethylene terephthalate, polybutylene terephthalate, and unsaturated polyester, acrylic resins such as polyacrylic and polymethyl methacrylate, epoxy resins, phenol-based resins, polyamide-based resins, polyimide-based resins, polysulfone resins, polyvinyl alcohol, polyurethane resins, polycarbonate resins, polydimethylsiloxane resins, and combinations thereof may be used, and may be either synthetic resins or natural resins. The resin substrate may be made of one type of resin or a combination of two or more types of resins.

[0055] The resin substrate may be a resin substrate having a biomass degree. For example, a resin substrate containing a resin material containing a plant-derived resin material such as plant-derived polyethylene, polypropylene, or polyester may be used. The biomass degree can be adjusted by further including a cellulose component. The biomass degree is as follows: 14 This is the concentration of C and can be measured by accelerator mass spectrometry.

[0056] [2.2 Cellulosic materials] The resin substrate may contain a cellulose-based material. By adding an antistatic agent to a resin material containing a cellulose-based material, it is possible to expect an antistatic effect as well as an improvement in cellulose dispersibility. Examples of the cellulose-based material include cellulose powder, cellulose fibers (cellulose nanofibers, cellulose microfibrils), pulp, and modified products thereof (for example, modified products obtained by chemical modification such as oxidation, etherification, phosphate esterification, silane coupling, fluorination, and cationization).

[0057] When the cellulose-based material is a cellulose powder, the average particle size is preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 μm or more. This makes it possible to suppress scattering and improve mixability when the cellulose powder is added to a reaction system. The upper limit is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. This makes it possible to maintain the kneadability during the formation of an ion complex and the smoothness of the resulting ion complex. Therefore, the average particle size of the cellulose powder is preferably 20 to 100 μm, more preferably 25 to 80 μm, and even more preferably 30 to 60 μm.

[0058] In this specification, the average particle size is the particle size when the volume accumulation distribution is 50%. The volume accumulation distribution can be obtained by a laser scattering method. The following method can be exemplified as the measuring device and measuring conditions. Measurement equipment: Laser diffraction particle size distribution measurement equipment (Mastersizer 3000, Spectris, Inc., Malvern Panalytical Division) Measurement conditions: Add a sample to the measurement section in water stirred at 3500 rpm so that the scattering intensity is about 10%, and measure under the following conditions. Analysis: General Purpose Analysis Sensitivity: Emphasis Light scattering model: Mie theory

[0059] The apparent specific gravity of the cellulose powder is preferably 0.1 g / ml or more, more preferably 0.15 g / ml or more. This can suppress the deterioration of workability due to scattering when the cellulose powder is added to the reaction system. The upper limit is preferably 0.6 g / ml or less, more preferably 0.45 g / ml or less, and even more preferably 0.4 g / ml or less. This can suppress the deterioration of dispersibility due to the occurrence of precipitation when the cellulose powder is added to the reaction system. Therefore, the range of 0.1 to 0.6 g / ml is preferable, the range of 0.1 to 0.45 g / ml is more preferable, and the range of 0.15 to 0.4 g / ml is even more preferable.

[0060] In this specification, the apparent specific gravity is the mass of cellulose powder per unit volume (1 mL). The apparent specific gravity can be measured, for example, by putting a sample (e.g., 10 g) into a measuring cylinder (e.g., 100 mL capacity), tapping the bottom of the measuring cylinder until the height of the sample stops decreasing, measuring the volume by reading the scale on the flattened surface, and dividing the weight of the sample by the volume.

[0061] [2.3 Other added ingredients] The resin substrate may contain additives other than the cellulose-based material. Examples of the additives include known resin additives such as antioxidants, preservatives, stabilizers, solvents, and inorganic fillers (e.g., carbon fiber, talc, mica, titanium oxide, and silica), and are not particularly limited.

[0062] [2.4 Usage] The amount of antistatic agent used (amount of copolymer relative to 100% by weight of the resin substrate (including additive components, the same applies below)) is usually 1.0% by weight or more, preferably 1.5% by weight or more or 2.0% by weight or more, more preferably 2.5% by weight or more. The upper limit is usually 80% by weight or less, preferably 75% by weight or less, more preferably 70% by weight or less. Therefore, it is usually 1.0 to 80% by weight, preferably 1.5 to 80% by weight or 2.0 to 75% by weight, more preferably 2.5 to 70% by weight.

[0063] When the resin substrate contains a cellulose-based material, the ratio of the content of the cellulose-based material to the content of the resin substrate is usually 5 / 95 or more, preferably 10 / 90 or more, more preferably 15 / 85 or more. The upper limit is usually 80 / 20 or less, preferably 75 / 25 or less, more preferably 70 / 30 or less.

[0064] The above composition usually corresponds to the amount of each component blended when the composition is produced.

[0065] [2.5 Mixing method] The method of kneading (blending) the antistatic agent into the resin substrate is not particularly limited, and any commonly used method can be used. When kneading, a kneading machine may be used as necessary. When kneading, the system may be heated, and the heating temperature is, for example, 100°C or higher, preferably 150°C or higher. The upper limit is usually 250°C or lower, preferably 200°C or lower.

[0066] [2.6 Resin compositions, molded products] A resin composition containing an antistatic agent and a resin substrate can exhibit antistatic properties, and by molding the resin composition, a molded article having a good antistatic effect can be obtained. Examples of applications of the molded article include electronic parts (e.g., household appliances, trays for transporting semiconductors). EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto.

[0068] Production Example 1 (Production of Lignosulfonate (a-1)) Wood derived from Radiata pine was subjected to a sulfite treatment using a magnesium sulfite solution with a SO2 concentration of 4 g / 100 mL based on the sulfite cooking method at 140°C and pH 2 for 3 hours. The resulting composition was filtered, and the filtrate was adjusted to pH 5.0 with an aqueous sodium hydroxide solution. The filtrate was concentrated using a polysulfone-based ultrafiltration membrane with a molecular weight cutoff of 20,000, and spray-dried using a spray dryer to obtain lignin sulfonate (sodium salt) (a-1).

[0069] Production Example 2 (Production of Lignosulfonate (a-2)) Wood derived from Radiata pine was treated with sulfite at 140°C and pH 2 for 3 hours using a magnesium sulfite solution with a SO2 concentration of 4 g / 100 mL based on the sulfite cooking method, and the resulting composition was filtered, and the filtrate was adjusted to pH 12 with an aqueous sodium hydroxide solution, oxidized by air bubbling at 140°C for 30 minutes, adjusted to pH 3 with 70% sulfuric acid, and the solid matter was collected by filtration to obtain lignin sulfonate (sodium salt) (a-2).

[0070] Production Example 3 (Production of Lignosulfonate (a-3)) Wood derived from Radiata pine was treated with sulfite at 140°C and pH2 for 3 hours using magnesium sulfite solution with SO2 concentration of 4g / 100mL based on the sulfite cooking method, and magnesium hydroxide solution was added to the obtained composition so that the solid content was 9wt%, and the mixture was kept at 90°C for 4 hours to cause an alkaline reaction. Next, oxygen was blown in at an oxygen pressure of 200kPa for 2 hours to perform an oxygen treatment, the pH was adjusted to 7.0, and the mixture was spray-dried with a spray dryer to obtain lignin sulfonate (sodium salt) (a-3).

[0071] Example 1 Into a 1L separable flask, 200g of water, 65g of lignin sulfonate (a-1) as compound (i), 35g of poly(ethylene oxide) monophenyl ether (average mole number of ethylene oxide added: 100) as compound (ii), 10g of 37% formaldehyde aqueous solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L calcium hydroxide aqueous solution and 20g of 31% sodium hydroxide aqueous solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-1).

[0072] The weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-1) was (I) / (II) = 65 / 35, the peak area ratio of the high molecular weight component was 93%, the reaction rate of compound (i) with compound (ii) was 80%, and the weight average molecular weight of compound (b-1) was 40,000 (Table 1).

[0073] Example 2 Into a 1L separable flask, 200g of water, 45g of lignin sulfonate (a-1) as compound (i), 55g of poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 50) as compound (ii), 10g of 37% aqueous formaldehyde solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L aqueous calcium hydroxide solution and 20g of 31% aqueous sodium hydroxide solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-2).

[0074] The weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-2) was (I) / (II) = 45 / 55, the peak area ratio of the high molecular weight component was 90%, the reaction rate of compound (i) with compound (ii) was 95%, and the weight average molecular weight of compound (b-2) was 30,000 (Table 1).

[0075] Example 3 Into a 1L separable flask, 200g of water, 30g of lignin sulfonate (a-1) as compound (i), 70g of poly(ethylene oxide) monophenyl ether (average mole number of ethylene oxide added: 25) as compound (ii), 10g of 37% formaldehyde aqueous solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L calcium hydroxide aqueous solution and 20g of 31% sodium hydroxide aqueous solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-3).

[0076] The weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-3) was (I) / (II) = 30 / 70, the peak area ratio of the high molecular weight component was 94%, the reaction rate of compound (i) with compound (ii) was 80%, and the weight average molecular weight of compound (b-3) was 55,000 (Table 1).

[0077] Example 4 Into a 1L separable flask, 200g of water, 35g of lignin sulfonate (a-2) as compound (i), 65g of poly(propylene oxide) monophenyl ether (average molar number of propylene oxide added: 100) as compound (ii), 10g of 37% formaldehyde aqueous solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L calcium hydroxide aqueous solution and 20g of 31% sodium hydroxide aqueous solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-4).

[0078] The reaction weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-4) was (I) / (II) = 35 / 65, the peak area ratio of the high molecular weight component was 92%, the reaction rate of compound (i) with compound (ii) was 70%, and the weight average molecular weight of compound (b-4) was 80,000 (Table 1).

[0079] Example 5 Into a 1L separable flask, 200g of water, 70g of lignin sulfonate (a-3) as compound (i), 30g of poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 50) as compound (ii), 10g of 37% aqueous formaldehyde solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L aqueous calcium hydroxide solution and 20g of 31% aqueous sodium hydroxide solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-5).

[0080] The reaction weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-5) was (I) / (II) = 70 / 30, the peak area ratio of the high molecular weight component was 88%, the reaction rate of compound (i) with compound (ii) was 90%, and the weight average molecular weight of compound (b-5) was 30,000 (Table 1).

[0081] Example 6 Into a 1L separable flask, 200g of water, 20g of lignin sulfonate (a-3) as compound (i), 80g of poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 50) as compound (ii), 10g of 37% aqueous formaldehyde solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L aqueous calcium hydroxide solution and 20g of 31% aqueous sodium hydroxide solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-6).

[0082] The weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-6) was (I) / (II) = 20 / 80, the peak area ratio of the high molecular weight component was 86%, the reaction rate of compound (i) with compound (ii) was 90%, and the weight average molecular weight of compound (b-6) was 90,000 (Table 1).

[0083] Example 7 Into a 1L separable flask, 200g of water, 30g of lignin sulfonate (a-1) as compound (i), 65g of poly(ethylene oxide) monophenyl ether (average mole number of ethylene oxide added: 25) as compound (ii), 5g of p-hydroxybenzoic acid, 10g of 37% aqueous formaldehyde solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L aqueous calcium hydroxide solution and 20g of 31% aqueous sodium hydroxide solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-7).

[0084] The reaction weight ratio of each constituent unit contained in the obtained lignin derivative compound was (I) / (II) = 30 / 70, the peak area ratio of the high molecular weight components was 93%, the reaction rate of compound (i) with compound (ii) was 95%, and the weight average molecular weight of compound (b-7) was 65,000 (Table 1).

[0085] Example 8 Into a 1L separable flask, 200g of water, 70g of lignin sulfonate (a-1) as compound (i), 25g of poly(ethylene oxide) monophenyl ether (average mole number of ethylene oxide added: 25) as compound (ii), 5g of aniline sulfonate, 10g of 37% aqueous formaldehyde solution, 40g of 72% sulfuric acid, and 0.05g of Pronal 753 (manufactured by Toho Chemical Industry Co., Ltd.) as a defoaming agent were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining the mixture at 105°C for 10 hours. To the resulting aqueous solution, 80g of 250g / L aqueous calcium hydroxide solution and 20g of 31% aqueous sodium hydroxide solution were added, and the mixture was stirred for 1 hour, and then filtered to remove the resulting gypsum, to obtain a lignin derivative compound (b-8).

[0086] The reaction weight ratio of each constituent unit contained in the obtained lignin derivative compound (b-8) was (I) / (II) = 70 / 30, the peak area ratio of the high molecular weight component was 92%, the reaction rate of compound (i) with compound (ii) was 95%, and the weight average molecular weight of compound (b-8) was 25,000 (Table 1).

[0087] Comparative Example 1 An aqueous solution containing only lignin sulfonate (a-1) as compound (i) was used (Table 1).

[0088] Comparative Example 2 An aqueous solution containing only poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 100) as compound (ii) was used (Table 1).

[0089] Comparative Example 3 Into a 1 L separable flask, 200 g of water, 45 g of lignin sulfonate (a-1) as compound (i), and 55 g of poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 50) as compound (ii) were added, and the mixture was stirred at room temperature for 10 hours to obtain a mixture of compound (i) and compound (ii).

[0090] In the obtained mixture, the weight ratio of compound (i) to compound (ii) was (i) / (ii) = 45 / 55, the peak area ratio of the high molecular weight component was 45%, and the reaction rate of compound (i) with compound (ii) was 0%.

[0091] [Table 1]

[0092] [Preparation of kneaded base material] Polypropylene resin pellets, Wintech (registered trademark) WSX-03 (propylene-ethylene copolymer manufactured by Japan Polypropylene), cellulose powder, KC Flock W-100GK (manufactured by Nippon Paper Industries Co., Ltd.), and additives were mixed in a Labo Plastomill (registered trademark) (4M150; manufactured by Toyo Seiki Co., Ltd.) at a temperature of 180°C and a rotation speed of 150 rpm for 5 minutes to obtain a mixed base material, so that the total weight of the mixture was 40 g in terms of solid content.

[0093] As the additive, one of the following types was used. Sample solutions prepared in the examples and comparative examples Compatibilizer resin (Eumex 1010, Sanyo Chemical) Antistatic resin (Pellestat 300, Sanyo Chemical) When the additive contained moisture, it completely evaporated during kneading and was released outside the system.

[0094] The resulting kneaded base material was rolled at a temperature of 200° C. and a pressure of 5 MPa for 1 minute to obtain a test piece having a smooth surface and a size of about 10 cm square and a thickness of about 1 mm.

[0095] [Evaluation of cellulose dispersibility] The obtained test pieces were observed under a microscope, and objects having a length of 2.5 mm or more and an aspect ratio of 100 or more were determined to be unmixed cellulose fibers. The observation conditions were as follows: Observed with a field of view of 8mm square, magnification of 35x, and resolution of 5.2μm. · Different areas on the test specimen were observed five times in total, and the amount of unmixed cellulose fibers observed was counted.

[0096] The evaluation criteria were as follows: "Good": The number of unmixed cellulose fibers is 0 in a total of 5 observations. "△": 1 to 3 unmixed cellulose fibers were observed in 1 to 3 observations. "X": Three or more unmixed cellulose fibers were observed in one to three observations, or one or more unmixed cellulose fibers were observed in three or more observations.

[0097] [Measurement of surface resistivity] Measurements were performed in accordance with JIS K 6911 using a high resistivity meter "Hiresta-UP" (manufactured by Mitsubishi Chemical). A test piece made from the kneaded base material was placed on the Teflon (registered trademark) surface of a register table UFL (manufactured by Mitsubishi Chemical) as a measurement table under conditions of a temperature of 25°C and a humidity of 50%, and a URS probe (manufactured by Mitsubishi Chemical) was used as a probe, and the probe was lightly pressed against the center of the test piece and the measured value was recorded after 10 seconds. The above measurement was performed a total of five times for the same sample so that the measurement points did not overlap, and the average value was taken as the surface resistivity (Ω / sq.).

[0098] 〔comprehensive evaluation〕 The evaluation of cellulose dispersibility and the measurement results of surface resistivity were combined to give an overall evaluation according to the following criteria. "Good": The cellulose dispersibility is evaluated as "good" and the measured surface resistivity is 5.0×10 12 below. "△": The cellulose dispersibility is rated "△" and the measured surface resistivity is 5.0×10 12 or less, or the cellulose dispersibility is evaluated as "good" but the measured surface resistivity is 5.0×10 12 ~2.0×10 13 Range of. "X": Cellulose dispersibility is rated "X" and / or the measured surface resistivity is 2.0×10 13 Exceeds.

[0099] An overall rating of △ or above means that the product is practical.

[0100] The cellulose dispersibility, surface resistivity and overall evaluation results of the obtained kneaded base material are shown in Table 2.

[0101] [Table 2]

[0102] In the kneaded base material of only cellulose and PP without using additives, neither cellulose dispersibility nor surface resistivity was practical. In addition, in the case of a lignin sulfonic acid compound alone (Comparative Example 1), an aromatic water-soluble compound having an alkylene oxide chain alone (Comparative Example 2), and a mixture of a lignin sulfonic acid compound alone and an aromatic water-soluble compound having an alkylene oxide chain (Comparative Example 3), none of them improved both cellulose dispersibility and surface resistivity to a practical level.

[0103] In addition, the use of only the compatibilizer additive improves cellulose dispersibility but does not improve surface resistivity, and the use of only the antistatic additive improves surface resistivity but does not improve cellulose dispersibility, so that both performance properties cannot be achieved at the same time.

[0104] On the other hand, when the additives of Examples 1 to 8 were added, a small amount of the additives reduced the surface resistivity, and some of them exceeded the amount of the existing antistatic resins. In addition, when the additives were added to a substrate containing cellulose, the cellulose dispersibility was confirmed by increasing the amount of each additive.

[0105] These results show that the composition of the present invention can improve surface resistivity, and when the resin composition contains a cellulose component, it is expected that the cellulose dispersibility can also be improved, and therefore the composition can be used in products for electronic components and environmentally friendly products.

Claims

1. An antistatic agent for resins, comprising a lignin derivative compound containing the following structural units (I) and (II): (I): Structural unit derived from lignosulfonic acid compound (II): A structural unit derived from an aromatic water-soluble compound that contains at least an aromatic water-soluble compound having an alkylene oxide chain.

2. 2. The antistatic agent according to claim 1, wherein the aromatic water-soluble compound having an alkylene oxide chain comprises an aromatic water-soluble compound having an alkylene oxide chain with an average added mole number of 25 or more of alkylene oxide.

3. 3. The antistatic agent according to claim 1, wherein the weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is from 1 / 99 to 99 / 1.

4. 3. The antistatic agent according to claim 1, wherein the water-soluble aromatic compound further comprises an aromatic compound having a carboxyl group and / or an aromatic compound having a sulfo group.

5. 3. The antistatic agent according to claim 1, wherein the lignin derivative compound represented by the following formula has a peak area ratio of a high molecular weight component of 80% or more. Peak area ratio of high molecular weight components = (area value of high molecular weight components in GPC chart (280 nm)) / (area value of all components in GPC chart (280 nm))

6. A method for treating a resin surface, comprising kneading the antistatic agent according to claim 1 or 2 into a resin substrate.

7. A resin composition comprising the antistatic agent according to claim 1 or 2 and a resin substrate.

8. The resin composition according to claim 7, wherein the content of the antistatic agent is 1.5% by weight or more based on 100% by weight of the resin substrate.

9. The resin composition of claim 7 , wherein the resin substrate further comprises a cellulosic material.

10. A molded article made from the resin composition according to claim 7.

Citation Information

Patent Citations

  • Antistatic agent

    JP2018123306A

  • Antistatic agent for thermoplastic resin and applications thereof

    JP2018178042A